Influence of the Culture Medium Nitrogen Concentration on Alkaloid Profile and Reserpine Content of the Rauwolfia Serpentina Plant Roots - Panwar, G.S.; Guru, S.K. (Indian Forester, 2013)
In the present investigation, total nitrogen content of Rauwolfia serpentina plant parts collected from different localities and influence of culture medium nitrogen doses on the total alkaloid profile as well as on the reserpine production was studied. The total nitrogen content of R. serpentina plant parts, including roots (wild, cultivated and in vitro regenerated), leaves (wild and cultivated) and callus regenerated in MS and B5 medium, were estimated by Kjeldahl method. It was observed that the roots regenerated through in vitro culture in MS medium contained higher nitrogen content (7.6%) as compared to the cultivated and wild roots. The alkaloid profile of the R. serpentina roots and callus, regenerated in MS and B5 medium supplemented with different nitrogen doses (half, normal and double), revealed that the alkaloid contents increased with increasing medium nitrogen concentration. An increase of 1.96 fold in reserpine content observed in MS and B5 medium supplemented with double nitrogen doses, respectively.